IMPLEMENTASI SISTEM INFORMASI PERIZINAN MENEMPATI KIOS DAN LOS PASAR (STUDI KASUS PADA DINKUKMP KABUPATEN PURWOREJO) - Eko Cahyono, Damar (Politeknik Sawunggalih Aji, 2025)
After conducting research at the Office of Cooperatives, Small and Medium Enterprises, and Trade, problems were found regarding the licensing service process and data processing, which were deemed less efficient and accurate. The licensing process is carried out manually, which requires more time, energy, and costs, making performance inefficient. Another problem is the difficulty in structuring the license requirement documents from the applicant, which causes the need for sufficient space to store documents. In this project, the research method used is observation, interview, and literature study, so that an information system is produced to help service and data processing by using a web program and a database. The creation of a Licensing Information System for Occupying Market Stalls and Lots is needed to help the service process become more effective. In addition, data processing becomes faster and more accurate.